Synthesis, Spectral and Magnetic Studies of Newly Mixed-Ligand Complexes of 4-Formyl-Acetanilide Thiosemicarbazone and 3,4-Dihydrocinnamic Acid with Some Metal Ions - Shayma A. Shaker (E-Journal of Chemistry, 2010)
New complexes with thiosemicarbazone derivative and 3, 4-dihydrocinnamic acid were prepared and characterized by elemental analysis, determination of metal, IR, 1H NMR, electronic spectroscopy and magnetic measurements. The thiosemicarbazone derivative forms bidentate ligand complexes of the general formula, [M(Thz)(Caf)] where Thz = 4-formyl- acetanilide thiosemicarbazone, Caf = 3,4-dihydrocinnamic acid and M=Mn2+, Fe2+, Co2+, Ni2+, Cu2+, Zn2+, Cd2+ and Pb2+. The IR and 1H NMR spectra indicates that the (Thz) was coordinated with the metal ions through the N and S atoms and the (Caf) was negatively charged bidentat ligand and was coordinated with the metal ions through the two O atoms. Electronic spectra and magnetic susceptibility measurements of the solid complexes indicates the tetrahedral geometry around the Mn2+, Fe2+, Co2+, Ni2+, Zn2+, Cd2+ and irregular tetrahedral geometry around Pb2+ ion while the Cu2+ complex has squar planer geometry.